Synthesis and Characterization of Maleic Acid-Butyl Acrylate Copolymers - CHAUHAN, ASHA (Asian Journal of Chemistry, 2010)
In the present work, the polymerization of maleic acid-butyl acrylate using emulsion polymerization has been reported.